2022
DOI: 10.1136/bmjno-2022-000291
|View full text |Cite
|
Sign up to set email alerts
|

Nationwide survey of Lambert-Eaton myasthenic syndrome in Japan

Abstract: BackgroundThere was no nationwide epidemiological study of Lambert-Eaton myasthenic syndrome (LEMS) in Japan; therefore, we conducted a nationwide survey.MethodsFor the first survey, we sent survey sheets to randomly selected medical departments (n=7545) to obtain the number of LEMS who visited medical departments between 1 January 2017 and 31 December 2017. For the second survey, we sent survey sheets to the corresponding medical departments to obtain clinical information on LEMS.ResultsWe received 2708 respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The prevalence of LEMS in Japan was estimated to be 0.27 per 100 000 44 . Core symptoms of LEMS are weakness of proximal extremities, decreased tendon reflexes and autonomic symptoms.…”
Section: Diagnostic Criteria Of Lemsmentioning
confidence: 99%
“…The prevalence of LEMS in Japan was estimated to be 0.27 per 100 000 44 . Core symptoms of LEMS are weakness of proximal extremities, decreased tendon reflexes and autonomic symptoms.…”
Section: Diagnostic Criteria Of Lemsmentioning
confidence: 99%
“…LEMS may occur as an autoimmune disease without malignancy (NT-LEMS), or as a paraneoplastic disorder (CA-LEMS) that is most commonly associated with small cell lung carcinoma (SCLC) [ 2 , 3 ]. LEMS is a rare disease with a prevalence of 2.7 per million population, and 54%–71.4% of LEMS patients have concomitant or subsequent SCLC [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…
Recently, a nationwide survey of Lambert-Eaton myasthenic syndrome (LEMS) was conducted by the Ministry of Health, Labour and Welfare research group and reported that the number of LEMS patients in Japan in 2017 was estimated to be 348. 1 In September 2021, the P/Q-type voltage-gated calcium channel (VGCC) antibody assay for the diagnosis and treatment of LEMS was covered by insurance. Furthermore, in May 2022, practical guidelines for myasthenia gravis (MG) and LEMS 2022 were compiled by the Japan Neurological Society.
…”
mentioning
confidence: 99%